2016
DOI: 10.1111/1365-2745.12669
|View full text |Cite
|
Sign up to set email alerts
|

Trait‐associated loss of frugivores in fragmented forest does not affect seed removal rates

Abstract: Summary1. Seed dispersal by frugivorous animals forms the basis for regeneration of numerous plant species. Habitat fragmentation has been found to be one major factor perturbing frugivore communities and dependent plant species. Yet, community-wide consequences of fragmentation for both frugivore and plant communities are still hardly understood. 2. Here, we studied the effects of habitat fragmentation on the seed removal by frugivorous birds and mammals from nine fleshy-fruited plant species in Białowie_ za … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 74 publications
4
46
0
Order By: Relevance
“…2), which could be explained by both bird and plant traits (Farwig et al 2017). For the bird perspective, it has been shown that medium-sized birds are not as sensitive to disturbance as large-bodied birds (Moore and Swihart 2007;Breitbach et al 2010), as the remaining forests still provide adequate shelter and food for the persistence of medium-sized birds in disturbed habitats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2), which could be explained by both bird and plant traits (Farwig et al 2017). For the bird perspective, it has been shown that medium-sized birds are not as sensitive to disturbance as large-bodied birds (Moore and Swihart 2007;Breitbach et al 2010), as the remaining forests still provide adequate shelter and food for the persistence of medium-sized birds in disturbed habitats.…”
Section: Discussionmentioning
confidence: 99%
“…For the bird perspective, it has been shown that medium-sized birds are not as sensitive to disturbance as large-bodied birds (Moore and Swihart 2007;Breitbach et al 2010), as the remaining forests still provide adequate shelter and food for the persistence of medium-sized birds in disturbed habitats. For the plant perspective, plant traits of T. chinensis also determined the persistence of birds in disturbed habitats, thus affecting the foraging behaviour of birds (Farwig et al 2017;Muñoz et al 2017). Crop size, fruit size, and height of T. chinensis could be good advertisements that attract birds (crop size: 4000 per mother tree; fruit weight: 7 g; height: 25-45 m) (Jordano and Schupp 2000;Martinez et al 2008;Herrera and García 2009;Li et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the fact that generalist species could reorganize their interactions by replacing their partners suggested that species in our generalized plant-frugivore assemblage were efficient when tracking fruit resources and showed strong context dependency despite the interannual spatial variability Chamberlain et al, 2014). Since seed removal has been shown to not be strongly affected by possible shifts in the frugivory community (Farwig et al, 2017), temporal inconsistency in the spatial patterns of interaction might have long-term effects on seed-dispersal processes, especially in such degraded and fragmented systems. Although denser seed rain is expected in areas concentrating pairwise interactions, as suggested by the typically higher density of dispersed seeds under fruiting canopies (García et al, 2005b;Herrera and García, 2010;Carlo et al, 2013), this temporal and spatial dynamism might be relevant for diluting density-dependent seed mortality, favoring genetic exchange, interspecific seed transfer (García et al, 2007) and promoting seed deposition and forest regeneration in open areas (Martínez and García, 2015b).…”
Section: Interannual Variability In the Spatial Distribution Of Pairwmentioning
confidence: 95%